MEDIA SOSIAL DAN PENGEMBANGAN HUBUNGAN INTERPERSONAL REMAJA DI SIDOARJO - Totok Wahyu Abadi; Fandrian Sukmawan; Dian Asha Utari (Kanal: Jurnal Ilmu Komunikasi, 2013)
The purpose of this study is to analyze and explain the use of social media among teenagers, the development of interpersonal relationships, and the influence of social media on the development of adolescent interpersonal relationships in Sidoarjo. This research, which involves a hundred high school students as the respondents, uses explanative approach. Through random sampling of data collection, the data were analyzed using descriptive statistics analyzing techniques and multiple regression. The results showed that the use of social networking sites by teenagers is much motivatedly aimed to 1 ) obtain a variety of information, 2 ) strengthen relationships among users of the site , 3 ) release tension, 4 ) meet emotional needs , and 5 ) improve self-confidence. The development of relationship made by teenagers is dominantly aimed to search identity information, ideas or thoughts, as well as the address of the user account. The level of development of interpersonal relationships ( friendships ) through social networking is at 68.7 %. The use of social networking sites which affect the development of adolescent interpersonal relationships in Sidoarjo is at 43.4 % .